SLACK INCLUDING SCHEME, SELF-ESTEEM IDEALISM, RELATIVISM AND BUDGET EMPHASIS UPON THE BUDGETARY SLACK BEHAVIOR AT PT PEGADAIAN - Peilouw, Christian Timotius; Naiola, Fransiscus Nicodemus; Elim, Meyulinda Aviana; Oktariyana, Made Denny (Unitri Press, 2024)
Purpose: This research aims to obtain empirical evidence of the effect of slack inducing compensation schemes, self-esteem, idealism, relativism, budgetary emphasis on budgetary slack. This research was conducted in attempts to examine the factors that influence the budgetary slack based on three aspects, namely economics, psychology, and sociology. Methods: The research used in this study was a quantitative approach. The research population is structural employees of PT Pegadaian (Kupang City and Ende City). Sampling technique with stratified random sampling method. Questionnaires are used as data collection techniques. The hypothesis was tested using multiple regression analysis by using IBM SPSS Statistic 25.0. Result and discussions: Based on statistical analysis, it shows that slack inducing compensation schemes, relativism and budgetary emphasis have a positive effect on budgetary slack. Meanwhile, idealism has a negative effect on the budgetary slack. Last, self-esteem has no effect toward budget gap but has a positive direction on budgetary slack.